The Application of the IMB Model as Primary Prevention on Adolescent’s Premarital Sexual Intention - Linda Suwarni; Selviana Selviana; Ufi Ruhama; Iskandar Arfan (International Journal of Public Health Science (IJPHS), 2017)
Previous studies showed the information, motivation, and behavioral skills (IMB) model could be used to predict and prevent reducing sexual risk behaviors. This paper examines the effectiveness of IMB interventions in reducing adolescent’s premarital sexual intentions. A quasy experimental nonequivalent pretest-posttest control group design was conducted among 250 students in 20 secondary schools in Pontianak with intervention IMB models and 100 students in the control group. There was a significant differences of information (delta mean = 3.008; 95% CI = 2.329 to 3.687; p value = 0.0001), motivation (delta mean = 1.532; 95% CI = 0.846 to 2.218; p value = 0, 0001), and skills to refuse or delay premarital sexual behavior (delta mean = 1.604; 95% CI = 0.629 to 2.579; p value = 0.001) on adolescents between before and after the application of the IMB model in secondary students in pontianak, Indonesia. In addition, there were significant differences intention adolescents in the control group and the experimental between before and after the IMB intervention (p value < 0.05). IMB model could be applied as primary prevention on adolescent’s premarital sexual intention through integration in school subjects. It is needed a support and debriefing skills in teachers.